2013
DOI: 10.1103/physreva.87.052713
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of the lithium2p2sphotoabsorption spectra perturbed by atomic hydrogen

Abstract: This work proposes a theoretical study of the Li(2p ← 2s) photoabsorption spectra perturbed by ground hydrogen atoms. The temperature effect on the far-wing spectra is examined in the temperature range 4000-20 000 K. For this purpose, the ground and excited LiH potential curves and the transition dipole moments that connect them are constructed from ab initio data. The investigation shows that the profile spectra are dominated at all temperatures by the singlet A ← X transitions and exhibit in the red wing a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…We compare the MSDFT potential energy curves to MS-CASPT2 results; both the qualitative trends and quantitative results from MS-CASPT2 calculations agree well with more complete or more accurate studies. , The present MSDFT method does not involve the high cost of a SA-CASSCF computation, but it includes all dynamic correlation at the stage of diabatic (basis) state construction, yielding results comparable or better than the more expensive MS-CASPT2 calculation. Furthermore, the number of configurations in the active space is smaller in the present method (12 determinants vs 45 in the (2,9)-CAS) – an advantage of the DTS scenario).…”
Section: Results and Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…We compare the MSDFT potential energy curves to MS-CASPT2 results; both the qualitative trends and quantitative results from MS-CASPT2 calculations agree well with more complete or more accurate studies. , The present MSDFT method does not involve the high cost of a SA-CASSCF computation, but it includes all dynamic correlation at the stage of diabatic (basis) state construction, yielding results comparable or better than the more expensive MS-CASPT2 calculation. Furthermore, the number of configurations in the active space is smaller in the present method (12 determinants vs 45 in the (2,9)-CAS) – an advantage of the DTS scenario).…”
Section: Results and Discussionmentioning
confidence: 56%
“…6971,7375 The present MSDFT method does not involve the high cost of a SA-CASSCF computation, but it includes all dynamic correlation at the stage of diabatic (basis) state construction, yielding results comparable or better than the more expensive MS-CASPT2 calculation. Furthermore, the number of configurations in the active space is smaller in the present method (12 determinants vs 45 in the (2,9)-CAS) – an advantage of the DTS scenario).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present discussion, it provides an interesting example to model multiple adiabatic states by a diabatic representation. The dissociation curves of LiH have been intensively investigated, and we have shown that it is sufficient to use seven VB basis states in MSDFT to describe quantitatively the energies of the four lowest singlet states in comparison with experiments and MS-CASPT2 calculations . The seven VB configurations, in order of increasing energy (Supporting Information), except the first, include the |Ψ ion [(Li + )­(H – )]⟩ ionic structure, the dissociation limits of the Li atom in the 2s, 2p, 3s, and 3p states, along with an excited configuration for the H­(2s) atom and the reverse ionic configuration |Ψ – [(Li – )­(H + )]⟩.…”
mentioning
confidence: 99%